Hot tensile deformation and fracture behaviors of a typical ultrahigh strength steel. (November 2019) - Wen, DongXu; Wang, JiaKai; Wang, Kang; Xiong, YiBo; Huang, Liang; Zheng, ZhiZhen; Li, JianJun
Abstract: The hot tensile deformation and fracture behaviors of a typical ultrahigh strength steel are investigated by isothermal uniaxial tensile experiments over the tensile temperatures of 900–1150 °C and strain rates of 0.01–10  s - 1 . By combining the results of tensile tests and microstructural observation, the effects of deformation processing parameter (strain rate and tensile temperature) on the macroscopic plastic deformation behaviors, microscopic fracture morphologies and microstructural evolution are clarified. The studies indicate that the hot tensile behavior of the studied steel is greatly influenced by the competition of damage evolution, work hardening, and dynamic softening. With the increased strain rate, the strain rate sensitivity coefficients decrease, but the value of elongation to fracture increase from 0.38 to 0.50. The variations of microvoids or cracks in amounts and sizes show an increasing trend with the increased strain rate or the decreased tensile temperature. At the low tensile temperature (900 °C), the poor capability of necking diffusion hardly prevents the strain localization, and the mesoscopic damages easily take place. As the strain rate increases from 0.01 to 10  s - 1, the neat fracture morphologies gradually change to the serrated. The main ductile fracture mechanisms transform from the intergranular fracture at the high tensile temperature and low strain rate to the transgranular fracture at the low tensile temperature and high strain rate. Highlights: The hot tensile deformation and fracture behaviors of a typical ultrahigh strength steel are studied. With the increased strain rate, the strain rate sensitivity coefficient decreases, but the elongation to fracture increases. The main fracture mechanisms transform from the intergranular to transgranular fracture with the decreased tensile temperature.